ANALISIS SPASIAL PERUBAHAN PENGGUNAAN LAHAN DENGAN DAYA DUKUNG TATA AIR DAERAH ALIRAN SUNGAI (DAS) KREO DI KOTA SEMARANG - Utami, Putri; Aji, Ananto; Juhadi, Juhadi (Geo-Image, 2017)
This research aims to: 1) identify and assess the changes of landuse of watershed Kreo in 2005-2015 2) compute, classify, and analyze the carrying capacity of water system based on the criteria, namely the value of coefficient of flow regimes (KRS), the annual flow coefficient (KAT), flood occurred, and the index of water use (IPA) of watershed Kreo in 2005-2015 3) analyze the effects of landuse change on the carrying capacity of water system of DAS Kreo in 2005-2015. The research method is qualitative and quantitative descriptive research method with the object of research is the effect of changes in land use in the watershed Kreo that may affect the carrying capacity of watershed hydrology. Data analysis techniques used in the study is the analysis of image interpretation, analysis the carrying capacity of water system, a qualitative and quantitatif descriptive analysis. The result of this research is the landuse change affect to the results of the carrying capacity calculation of river catchment area water management. Jatibarang Reservoir extends the positive impact that decrease the coefficient value of the flow regime (KRA) and the index of water use (IPA).